ADOPSI INOVASI USAHA KECIL DAN MENENGAH (UKM) DI SURAKARTA TERHADAP SISTEM PERBANKAN SYARIAH - Kussudyarsana Kussudyarsana (Muhammadiyah University Press, 2010)
This article tries to explain the adoption innovation phenomenon of sharia banking in Surakarta, especially for small-scale enterprises in Surakarta. This paper tries to investigate some factors that are predicted stimulate the owners of small enterprises to adopt or not to adopt the sharia banking. Those factors were principle of religion about interest, profit sharing, financial risk, cost of fund and banking facility. Research suggests that there were no significant impact of all factors except profit sharing. To measure how they would adapt we tested by several factors of Rogers model such as relative advantage, compatibility, complexity, trialibility, and observability. The result showed that this innovation could be having a relative advantage and compatibility, had a significant effect on the adoption of innovation but not for three others factors. To test the hypothesis we use regression analysis, cross tabulation and chi-square statistic.